Uso de los materiales educativos y el pensamiento matemático en niños de la Institución Educativa Inicial UNAP María Reiche, San Juan 2022 - Huaynacari Chavez, Anita del Jesus (2024)
The primary objective of this study was to determine the level of relationship between the use of educational materials and the level of mathematical thinking in children of the Institution Educative Initial UNAP María Reiche Sa Juan 2022. To carry out this purpose, a research approach of a relational nature, supported by a non-experimental design with cross-sectional correlational characteristics. The population under study included all the children enrolled in the UNAP María Reiche Initial Educational Institution, and a census sampling was carried out that included the participation of the 155 subjects involved in the research. Data collection was carried out through observation. To ensure the validity of the instruments used, they underwent an evaluation process by experts. The analysis of the data revealed a Spearman's Rho correlation coefficient of 0,755 between the variables of use of educational materials and mathematical thinking. This value indicates a significant correlation between both variables, it was concluded that there is a relationship between the use of educational materials and mathematical thinking in the children of the UNAP María Reiche San Juan Initial Educational Institution in 2022.